THE COMMUNITY EMPOWERMENT IN DEVELOPING SUNDA SNACK BUSINESS THROUGH THE UTILIZATION OF CSR ASSISTANCE - Riany Laila Nurwulan; Abu Huraerah; Nina Kurniasih (SEAN Institute, 2022)
This research aims to examine and analyze the use of corporate social responsibility assistance PT. Tirta Investama (Aqua) through community empowerment for glass chip business actors in Kasomalang District, Subang Regency, which is one of the snacks in Pasundan land. By using the Triple Bottom Line (3P) concept from John Elkington (1998), regarding corporate social responsibility (CSR), this research focuses on the social sector, namely the implementation of community empowerment for business actors. Community Empowerment uses the concept proposed by Dubois in Shera (1992:2) that empowerment implies both the process and the result. As a process of empowerment to increase the strength of the individual and interpersonal. As a goal, empowerment is a final expression, namely the acquisition of certain abilities. The approach in this research is qualitative, and the selection of informants is carried out using a purposive technique. The data collection techniques used were observation, interviews, and documentation. The data analysis uses the stages of data reduction, data presentation, and drawing conclusions and verification. The data validity technique used is source triangulation. The results of this research indicate that the process of implementing community empowerment is the application of strategies in community empowerment, especially through training for the poor, which includes motivation, awareness raising and skills training, self-management, resource mobilization, network development and development. Meanwhile, the result is that business actors have increased in terms of: a. Level of awareness and desire to change (power to). b. Ability level increases capacity to gain access (power within). c. The level of ability to face obstacles (power over). d. The level of ability to cooperate and solidarity (power with).